Time Dysperception Perspective for Acquired Brain Injury - Piras, Federica; Piras, Fabrizio; Ciullo, Valentina; Danese, Emanuela; Caltagirone, Carlo; Spalletta, Gianfranco (Frontiers in Neurology, 2014)
Distortions of time perception are presented by a number of neuropsychiatric disorders. Here we survey timing abilities in clinical populations with acquired brain injuries in key cerebral areas recently implicated in human studies of timing. We purposely analyzed the complex relationship between cognitive and contextual factors involved in time estimation, as to characterize the correlation between timed and other cognitive behaviors in each group. We assume that interval timing is a solid construct to study cognitive dysfunctions following brain injury, as timing performance is a sensitive metric of information processing, while temporal cognition has the potential of influencing a wide range of cognitive processes. Moreover, temporal performance is a sensitive assay of damage to the underlying neural substrate after a brain insult. Further research in neurological and psychiatric patients will definitively answer the question of whether time distortions are manifestations of cognitive and behavioral symptoms of brain damage and definitively clarify their mechanisms.